Contrasting Effects of Histone Deacetylase Inhibitors on Reward and Aversive Olfactory Memories in the Honey Bee - Gabrielle A Lockett; Fiona Wilkes; Paul Helliwell; Ryszard Maleszka (Insects, 2014)
Much of what we have learnt from rodent models about the essential role of epigenetic processes in brain plasticity has made use of aversive learning, yet the role of histone acetylation in aversive memory in the honey bee, a popular invertebrate model for both memory and epigenetics, was previously unknown. We examined the effects of histone deacetylase (HDAC) inhibition on both aversive and reward olfactory associative learning in a discrimination proboscis extension reflex (PER) assay. We report that treatment with the HDAC inhibitors APHA compound 8 (C8), phenylbutyrate (PB) or sodium butyrate (NaB) impaired discrimination memory due to impairment of aversive memory in a dose-dependent manner, while simultaneously having no effect on reward memory. Treatment with C8 1 h before training, 1 h after training or 1 h before testing, impaired aversive but not reward memory at test. C8 treatment 1 h before training also improved aversive but not reward learning during training. PB treatment only impaired aversive memory at test when administered 1 h after training, suggesting an effect on memory consolidation specifically. Specific impairment of aversive memory (but not reward memory) by HDAC inhibiting compounds was robust, reproducible, occurred following treatment with three drugs targeting the same mechanism, and is likely to be genuinely due to alterations to memory as sucrose sensitivity and locomotion were unaffected by HDAC inhibitor treatment. This pharmacological dissection of memory highlights the involvement of histone acetylation in aversive memory in the honey bee, and expands our knowledge of epigenetic control of neural plasticity in invertebrates.